Indicadores internos como alternativa ao óxido de crômio-III na determinação dos coeficientes de digestibilidade aparente pela Tilápia do Nilo - Silva, Rafael Lopes da [UNESP] (2015)
The objective of this study was to evaluate different methods of measuring digestibility in Nile tilapia fed two diets containing only plant origin ingredients or animal and plant origin ingredients. The methods evaluated were: crude fiber (CF), neutral detergent fiber (NDF), acid detergent fiber (ADF), hemicellulose, cellulose and lignin. Chromic oxide (Cr2O3; 0,1%) was added in both diets and used as standard external indicator. Groups of 10 juveniles of Nile tilapia (80,3±1,0 g) were allocated in six 80 L-cylindrical net cage, housed in six 250 L-circular feeding tanks and hand-fed to apparent satiation eight times a day. One hour after the last feeding, the cages were transferred and kept overnight into six 300 L-cylindrical conical feces collection tanks coupled to collectors. Fish were feed in an independent system from feces collection system in order to avoid the presence of feed in the feces samples. The ADC of dry matter (DM), energy and nutrients (crude protein, phosphorus and amino acids essentials and non essentials) were obtained by the difference in the level of internal indicators present in the diets and feces and compared to those obtained by the use of Cr2O3 by Dunnett's test. The diet containing only plant origin ingredients had a higher ADC of DM, energy and nutrients (P<0,05). The utilization of CF, NDF, ADF, hemicellulose and lignin fraction as indicators were inefficient in all analyzed variable in animal and plant origin ingredients diet (P<0,05). However, in the diet containing only plant origin ingredients the fractions ADF and cellulose were similar to Cr2O3 to determine ADC of DM, energy and all nutrients. Therefore, these fractions are indicated for investigation of ADC by Nile tilapia fed diets containing only plant origin ...